Teknik Role Playing Pada Anak Tuna Grahita untuk Meningkatkan Keterampilan Interpersonal - Dara Intan Cahaya; Abu Bakar; Fajriani Fajriani (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
Generally, children with mental retardation experience difficulties in social interaction, because children with mental retardation don't have the skills to build a good relationship with other people or don't have interpersonal skill. This research to see an overview of interpersonal skills of children with mental retardation in SDLB Negeri Banda Aceh before and after of treatment technique role-playing. The technique role-playing is a process of counseling for shaping behavior adaptive children with mental retardation, with a pleasant atmosphere and make children with mental retardation actively participate in simulate. The type of this research is pra-experiment with the form of one group pretest-posttest, the approach used in this research is mix method design. The data collection technique used observation and interview. The data analysis technique in this research using quantitative and qualitative analysis, quantitative was with Wilcoxon Signed Rank to see the comparison before and after treatment, which obtained the result of Z count equal to -2,201 with asymptotic significant for the two-way test of 0,028 0,05. Then the hypothesis testing in this study Ha is accepted and H0 is rejected. The technique of role-playing can be used to improve the interpersonal skills of children with mental retardation.